2020
DOI: 10.1371/journal.pone.0236986
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness diminishes the effects of age on white matter hyperintensity volume

Abstract: White matter hyperintensities (WMHs) are among the most commonly observed marker of cerebrovascular disease. Age is a key risk factor for WMH development. Cardiorespiratory fitness (CRF) is associated with increased vessel compliance, but it remains unknown if high CRF affects WMH volume. This study explored the effects of CRF on WMH volume in community-dwelling older adults. We further tested the possibility of an interaction between CRF and age on WMH volume. Participants were 76 adults between the ages of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…Observational studies suggest that physical activity and exercise may limit WMH. Two systematic reviews found physical activity to be associated with less WMH [17,18], and the effect appeared particularly prominent in older adults [19,20]. Both participating in physical activity and aerobic exercise training can improve cardiorespiratory fitness, which is suggested as a central mechanism for the effect of training on the brain [21].…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies suggest that physical activity and exercise may limit WMH. Two systematic reviews found physical activity to be associated with less WMH [17,18], and the effect appeared particularly prominent in older adults [19,20]. Both participating in physical activity and aerobic exercise training can improve cardiorespiratory fitness, which is suggested as a central mechanism for the effect of training on the brain [21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, age is an independent predictor of cardiovascular disease risk and therefore may explain its stronger association with WMH volume compared with PA (48). To further explore this complex relationship, authors have investigated the relationship between age, cardiorespiratory fitness (CRF; expressed as peak oxygen uptake (49)), and WMH volume. Johnson and colleagues (49) reported that CRF reduced the predictive effect of age on WMH, where older adults with greater CRF had lower WMH volume compared with older adults with lower CRF.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore this complex relationship, authors have investigated the relationship between age, cardiorespiratory fitness (CRF; expressed as peak oxygen uptake (49)), and WMH volume. Johnson and colleagues (49) reported that CRF reduced the predictive effect of age on WMH, where older adults with greater CRF had lower WMH volume compared with older adults with lower CRF. Although PA is closely associated with CRF (50), CRF is a direct, physiological measurement associated with endothelial and autonomic function, and a stronger predictor of cardiovascular disease risk compared with PA (51).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple systematic reviews have shown the positive effects of physical activity on human structural neuroplasticity. In general, higher cardiorespiratory fitness or doses of physical activity seem to have protective effects on gray matter 15 , 16 and white matter volumes 17 19 . Intriguingly, in light of the recent shift to home-based lifestyles, sedentariness is increasingly being shown as a separate risk factor.…”
Section: Introductionmentioning
confidence: 96%